Pengaruh Inflasi Terhadap Pembiayaan Murabahah Pada Bank Umum Syariah di Masa Pandemi Covid 19 - Nu’man Afif; Slamet Haryono (ITB AAS INDONESIA Surakarta, 2022)
The purpose of this study was to determine the effect generated by rupiah exchange rate inflation and the impact of the COVID-19 pandemic on the amount of fees charged to murabahah transactions at Indonesian Sharia Commercial Banks. The population that has been determined is all Islamic banks that are established and operating in Indonesia. To facilitate data collection, the authors grouped the sample data into two categories. The first is related to Islamic banking statistics issued by the OJK, and the second is related to inflation published by Bank Indonesia. The type of research chosen in this study uses quantitative methods, in order to facilitate the process of data analysis, so that the data obtained can be accounted. The results show that inflation has a negative but not significant effect on murabahah financing and the corona virus has a positive and significant effect on murabahah financing.